2007
DOI: 10.3748/wjg.v13.i41.5486
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of gastroesophageal reflux disease in Shiraz, southern Iran

Abstract: GERD is more common in females, rural and illiterate subjects and correlated with consumption of pickles, occurrence of headache, psychological distress, dyspepsia, halitosis, anxiety, nightmare and restlessness, and a family history of GERD and aspirin intake, but the correlation was negative with consumption of fat and fiber intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
63
4
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 33 publications
12
63
4
1
Order By: Relevance
“…Also, in our region, the presence of H. pylori is more common, particularly in men (25). As in other studies, the prevalence of GERD increased with age, obesity, physical inactivity, a low education level, and with stress (11,26,27), but we did not observe an association with smoking.…”
Section: Chirila Et Al Diet In Gerd and Dyspepsiacontrasting
confidence: 28%
“…Also, in our region, the presence of H. pylori is more common, particularly in men (25). As in other studies, the prevalence of GERD increased with age, obesity, physical inactivity, a low education level, and with stress (11,26,27), but we did not observe an association with smoking.…”
Section: Chirila Et Al Diet In Gerd and Dyspepsiacontrasting
confidence: 28%
“…Jansson et al [20] , in a large population-based study, revealed in Norway, positive association between low socioeconomic status (based on occupation, education and maternal deprivation) and reflux symptoms. In a study in southern Iran, the prevalence of GERD was significantly higher in rural and illiterate subjects [9] . The relationship between lower educational level and the frequency of GERD which was discussed previously, probably reflects the action of certain unhealthy life style habits or less ability to modify such habits [14,21] .…”
Section: Discussionmentioning
confidence: 99%
“…The authors also found that the prevalence of GERD in Asia is either increasing or being recognized more frequently. In a study from urban and rural population of southern Iran, the prevalence of reflux symptoms occurring at least 3 times per week was 15.4% [9] . Hu et al [17] demonstrated that only 4.8% of Chinese population had GERD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Roesch-Ramos and colleagues indicated that the female/male ratio in GERD group was 2.3/1 which is in line with the predominance of female gender in GERD patients (2). On the other hand, despite a wide range of the rate of dental erosions in patients with GERD in different populations (3,4), the prevalence of DE is higher more than 3 times in comparison to our findings in a study in one of our referral university clinics (5).…”
Section: Dear Editormentioning
confidence: 57%